Beneficial Effects of Breastfeeding on the Prevention of Metabolic Syndrome Among Postmenopausal Women - Jin Suk Ra; Soon Ok Kim (Elsevier, 2020)
Summary: Purpose: This study aims to determine whether breastfeeding may have any beneficial effects on metabolic syndrome in a cohort of postmenopausal Korean women. Methods: A cross-sectional study with secondary data analysis was conducted using the cohort in the Korean Genome and Epidemiology Study. Data from 1,983 postmenopausal women were analyzed by logistic regression analysis. Controlled covariates were chosen based on a biopsychosocial model and included age, family history of hypertension; type 2 diabetes mellitus; and cerebro-cardiovascular diseases, body mass index, age of menarche, parity, socioeconomic status of family, educational level, past or current smoking experience, and current alcohol consumption experience. Results: Breastfeeding experience and duration were not significantly associated with a decreased likelihood of metabolic syndrome among postmenopausal women. However, breastfeeding experience (adjusted odds ratio [AOR]: 0.52 [p = .010]) and a total duration of breastfeeding exceeding 3 months were significantly associated with decreased likelihood of abdominal obesity (≥3 and < 6 months: AOR: 0.49 [p = .014]; ≥6 and < 12 months: AOR: 0.51 [p = .009]; ≥12 months: AOR: 0.56 [p = .024]). Conclusion: Our findings indicate that breastfeeding might have beneficial effects on reducing abdominal obesity in postmenopausal women. Health-care providers should publicize beneficial long-term effects of breastfeeding on the prevention of abdominal obesity, a component of metabolic syndrome.